Effectiveness of Topical Anesthetics in Pain Management for Dermal Injuries: a systematic review. - Navarro-Rodriguez, Juan Manuel; Suárez-Serrano, Carmen; Martín-Valero, Rocío; Marcén-Román, Yolanda; De La Casa-Almeida, María (MDPI, 2021)
The treatment of dermal injuries is associated with pain in both adult and pediatric populations. We reviewed traditional treatments for controlling the pain of these lesions, such as infiltrated local anesthetics and topical local anesthetics. The objective of this review was to elucidate the efficacy of topical anesthetics in reducing the pain of dermal injuries, as well as the efficacy of topical anesthetics versus other anesthetics, or versus a placebo. Methodology: a systematic review was carried out by searching Medline (PubMED), Scopus, Cinahl, Cochrane, Lilacs, and ENFISPO for randomized clinical trials on the control of pain in dermal lesions through the use of topical anesthetics, versus a placebo or versus another anesthetic. Results: twelve randomized clinical trials with a total of 952 patients were included. Seven studies analyzed the efficacy of topical anesthetics compared to a placebo, and six of them observed statistically significant differences in favor of the experimental group. Five studies analyzed the efficacy of topical anesthetics compared to other anesthetics or sedatives; three of them observed statistically significant differences in favor of the experimental group, and two found no difference between the anesthetics analyzed. Conclusion: topical anesthesia is a useful method for pain control, is safe compared to other traditional methods, and offers a satisfactory form of pain relief in relation to infiltration anesthesia and compared to placebo.
Keywords: Piel - Heridas y lesiones; Anestésicos; Administration; Topical; Anesthetics; Wounds and injuries